(untitled) (American Journal of Economics and Business Innovation, 2023)
The purpose of this study was to determine the effects of social innovation on the resilience of one-acre fund household livelihoods. Resilience is the ability to bounce back after a period of such shocks. . In that connection, there is a need to innovate alternatives that optimize resilience. Innovation has been studied in terms of technological innovation, business innovation, and or general innovation but not social innovation in connection to resilience. Social innovation uniquely matches resilience efforts at the vulnerable households’ level. However, this connection has not been studied rigorously. The findings revealed that social innovation contributed statistically significantly to resilience of one-acre fund household livelihoods (β =.832, p=.000) and accounted for 69.3% change in resilience of one-acre fund household livelihoods ΔR2=0.693, ΔF (1, 308) =167.748, p=.000.The study concluded that, if more emphasis is put in social innovation, more resilience of one-acre fund household livelihoods would be realized. Therefore, an enhanced leads to resilience for households’ livelihood. The study recommends that as a coping mechanism for food insecurity, farmers should adopt an acre fund model. this study advises the policymakers to consider the production of maize by use of one acre fund skills like social innovation to minimize the inefficiency levels and increase production by minimizing the cost of inputs and cost of capital The study highlights the applicability of social innovation in a new context and further facilitates creation of knowledge and growth of literature in the social innovation sphere.